Various Forms of Tuberculosis in Patients with Inflammatory Bowel Diseases Treated with Biological Agents - Adam Krusiński; Anna Grzywa-Celińska; Katarzyna Szewczyk; Luiza Grzycka-Kowalczyk; Justyna Emeryk-Maksymiuk; Janusz Milanowski (Hindawi Limited, 2021)
Although there are undeniable advantages of treatment of the inflammatory bowel diseases, Crohn's disease, and ulcerative colitis, with biological agents, the increased susceptibility to tuberculosis should not be ignored. Tuberculosis is an infectious disease caused by the Mycobacterium tuberculosis complex which includes M. tuberculosis, M. bovis, and M. africanum. Primary tuberculosis is uncommon in the setting of inflammatory bowel disease: reactivation of latent tuberculosis is of greater concern. Consequently, latent infection should be excluded in patients who qualify for immunosuppressive treatments. Apart from the review of the literature, this article also presents three cases of different patterns of tuberculosis that occurred during treatment with infliximab, adalimumab, or vedolizumab. The first case reports a case of tuberculosis presenting as right middle lobe pneumonia. The second case featured miliary tuberculosis of the lungs with involvement of the mediastinal lymph nodes, liver, and spleen. The third patient developed a tuberculoma of the right parietal lobe and tuberculous meningitis. It is important to reiterate that every patient qualifying for a biologic agent should undergo testing to accurately identify latent tuberculosis, as well as precise monitoring for the possible development of one of the various forms or patterns of tuberculosis during treatment.